Supraclavicular flap for head and neck oncological reconstruction: A series of 62 cases - Giulia Godoy Takahashi; Renan Diego Américo Ribeiro; Vitor Penteado Figueiredo Pagotto; Thadeu Rezende Rangel Fernandes; Hélio Ricardo Nogueira Alves; Fábio de Freitas Busnardo; Rolf Gemperli (Revista Brasileira de Cirurgia Plástica)
Introduction: The oncological reconstruction of extensive defects in the head and neck requires the plastic surgeon to make a difficult decision between the use of free flaps and pedicled flaps. The supraclavicular flap is one of the main examples of a pedicled flap, being versatile, with a thin thickness and similar color to the region to be reconstructed. Method: A retrospective study was carried out by collecting data from medical records of patients admitted to the Cancer Institute of the State of São Paulo between December 2010 and March 2020. Results: Among the 62 patients reconstructed with a supraclavicular flap, 37 were male and 25 female. Fifty-eight patients (93.5%) had some associated comorbidity. In total, 27 complications related to the flap (43.5%) were recorded, 5 of which were total necrosis (8%). Conclusion: The supraclavicular flap plays an important role in head and neck oncological reconstructions and should be considered as an option in patients who are poor candidates for microsurgical flaps.